PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR MATERI OPERASI HITUNG BILANGAN BULAT PADA SISWA KELAS IV DI SD INPRES JE’NETALLASA - Aulia Bahri, Nurul; Irwan Akib; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Nurul Aulia Bahri. 2026. The Effect of Implementing the “Make a Match” Cooperative Learning Model on Fourth-Grade Students’ Learning Outcomes of Integer Arithmetic at SD Inpres Je’netallasa. Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I: Irwan, and Supervisor II: Ernawati The main research question in this study is whether the implementation of the “Make a Match” cooperative learning model affects fourth-grade students’ learning outcomes of integer arithmetic operations at SD Inpres Je'netallasa. This study aims to determine the effect of implementing the “Make a Match” cooperative learning model on students’ learning outcomes of integer arithmetic operations. This study is a pre-experimental study using a one-group pretest-posttest design. The research subjects were all 20 fourth-grade students at SD Inpres Je'netallasa. Data collection techniques used achievement tests in the form of pretests and posttests. The data analysis techniques used were descriptive statistical analysis, normality tests, homogeneity tests, and hypothesis testing, as well as N-Gain calculations. The results of the study indicate that the students’ average pretest score was 58.40, which falls into the moderate category, while the average posttest score was 82.10, which falls into the high category. The N-Gain calculation results indicate an improvement in students’ Learning Outcomes following the implementation of the Make a Match cooperative learning model. Based on the results of the hypothesis test, it was found that the implementation of the Make a Match cooperative learning model had a significant effect on the learning outcomes of integer arithmetic operations among fourth-grade students at SD Inpres Je'netallasa. Thus, it can be concluded that the Make a Match cooperative learning model has a positive effect on improving students' learning outcomes of integer arithmetic operations.